2004
DOI: 10.1038/sj.ijir.3901222
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the factors influencing erectile function after renal transplantation

Abstract: A total of 400 male renal transplant recipients (RTR) were investigated. Data on medical, sexual history, clinical examination and laboratory variables were collected. The severity of erectile dysfunction (ED) was assessed using the International Index of Erectile Function questionnaire. Univariate and multivariate logistic regression analyses were used to determine prognostic variables, which have independent impact on erectile function. ED was detected in 35.8% of the whole group. Current erectile function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…Earlier studies have determined the prevalence of ED following renal transplant to be between 54% and 66%. 10 The prevalence of ED in our study, with a sample size of 55 patients, was 51%, which is consistent with that reported in the current literature. Overall, 11 (20%), 6 (11%), 4 (7%) and 7 (13%) patients had mild, mild-moderate, moderate, and severe ED, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Earlier studies have determined the prevalence of ED following renal transplant to be between 54% and 66%. 10 The prevalence of ED in our study, with a sample size of 55 patients, was 51%, which is consistent with that reported in the current literature. Overall, 11 (20%), 6 (11%), 4 (7%) and 7 (13%) patients had mild, mild-moderate, moderate, and severe ED, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…The importance of increased age on the prevalence of ED in the renal transplant population has been verified in several studies. 5,10,11 In Malavaud and colleagues' study of 271 post renal transplant patients, the average age of patients with ED was 49.2 years old, compared with 44.5 years old for patients without ED. 5 The mean age of patients with ED after renal transplant in another study was 43.6 years old, compared with 34.9 years old in patients without ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other reports have suggested that as many as 48.9% 13 to 55.7% 11 of recipients continue to suffer ED. ElBahnasawy et al 9 found that erectile function improved in 40% of patients but deteriorated or remained unchanged in 18% and 42%, respectively, of patients 6 months post-transplantation. Notably, in a recent study of 78 KT recipients assessed with the IIEF, the ED rate increased from 87% preoperatively to 91% one year postoperatively, with a mean reduction of the EF domain from 18.48 to 17.55.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have suggested that erectile function significantly improves after successful renal transplantation, [5][6][7][8] especially when the surgery is performed at a younger age, 5 other studies have shown minimal effects of transplantation on erectile performance or even deterioration. [9][10][11][12] The overall prevalence of ED after KT remains high, ranging from 48.9% 13 to 55.7%. 11 The potential causative effects of ED in transplant recipients may include anxiety, medication side effects, impaired penile vascularity and failure to resolve hormonal abnormalities or underlying disease comorbidities.…”
Section: Introductionmentioning
confidence: 99%